Racism, identity and belonging: How do these factors interact for young Black people in predominantly white settings? - Mngaza, Siya (2020)
Background: Strong feelings of school belonging are closely associated with positive outcomes for children and young people, including academic achievement, engagement and motivation. Several perspectives conceptualise belonging as a transactional process, involving subjective evaluations, feelings of acceptance and evaluations of the immediate context. Within the UK, there is a lack of research that considers the experiences of belonging for minoritised young people. However, some studies indicate that the racial homogeneity of the school context plays a role within belonging ratings of ethnically minoritised children. This area of research is particularly pertinent in the case of Afro-Caribbean, or young ‘Black’ people, due to a range of educational disparities experienced within education.